Ideal cardiovascular health, handgrip strength, and muscle mass among college students: The fuprecol adults study (2019)
The American Heart Association established the 2020 Strategic Impact Goals to define the concept of ideal cardiovascular health (CVH) and the metrics needed to monitor it across populations. The purpose of this study was to investigate the relationship between handgrip strength, muscle mass, and ideal CVH among Colombian college students. Data from 1,835 college students were analyzed (1,128 female). Muscular strength was estimated using a hand-held dynamometer and normalized to body mass (normalized grip strength [NGS]). The percentage of body fat was determined for bioelectrical impedance analysis using tetrapolar whole-body impedance. Ideal CVH was defined as meeting the ideal levels of 4 behaviors (smoking, body mass index, physical activity, and diet adherence) and 3 factors (total cholesterol, fasting glucose, and blood pressure). Higher levels of NGS and muscle mass (relative to body mass) were associated with a higher number of ideal CVH metrics in both sexes (p for trend less than 0.001). For the total ideal CVH metrics scored on a continuous scale from 0 (all 7 poor) to 7 (all 7 ideal), a 1-metric increase was associated with reduced odds of weak NGS (33 and 36%) and low-medium muscle mass (28 and 34%) mass in men and women, respectively (all p less than 0.001). This study indicates that in Colombian college students, both handgrip strength and muscle mass are positively associated with the ideal CVH metrics. To reduce the possible future public health burden of muscular weakness, health professionals need to encourage the public to optimize lifestyle-related risk factors during the young adult stage. © 2019 National Strength and Conditioning Association.